Redefining Haute Couture: collaborations between the Chambre Syndicale de la Couture Parisienne and the French State in the 20th century (Revista de Ensino em Artes, Moda e Design, 2024)
The objective of this article is to think about the redefinitions of Haute Couture in the 20th century based on the collaboration between the Chambre Syndicale de la Couture Parisienne (CSCP) and the French State. The CSCP, founded in 1910, is an employers' union that organizes the various dimensions of the work of Haute Couture producers in Paris. We will affirm that the formation of the CSCP marks the institutionalization of what would become the field of Haute Couture, a relatively autonomous space of struggle. We will analyze the variation in the autonomy of this space in relation to the moment in which the union begins to establish collaborations with the French State. The cases of the legal institution of the Haute Couture nomenclature in 1945, and the implementation of the Aide-Textile aid between 1952 and 1961 will be taken as an example. We will see how certain aspects and rules of Haute Couture were changed as the transatlantic circulation of the segment was stimulated by the government . Thus, while the French State asserts its interests, the CSCP loses the monopoly control it previously exercised in defining this type of clothing production.
Keywords: haute couture; field; circulation; definition; french state